1
$\begingroup$

I have the following premises: A and (A ∨ B) → N

How can I prove A → N from this in a formal proof using FOL?

$\endgroup$
2
$\begingroup$

$\def\fitch#1#2{\begin{array}{|l}#1 \\ \hline #2\end{array}}$

$\fitch{ 1. A \quad Premise\\ 2. (A \lor B) \rightarrow N \quad Premise}{ \fitch{ 3. A \quad \ Assume} {4. A \lor B \quad \lor \ Intro \ 3\\ 5. N \quad \rightarrow \ Elim \ 2,4}\\ 6. A \rightarrow N \quad \rightarrow \ Intro \ 3-5}$

Note that this proof never used premise 1, as indeed $(A \lor B) \rightarrow N$ follows from $A \rightarrow n$ alone; it is an example of the valid inference pattern called Strengthening the Antecedent. Are you sure $A$ was an actual premise?

$\endgroup$
  • $\begingroup$ Thank you. This is exactly what I needed. $\endgroup$ – Daryn Wilkinson Aug 6 '17 at 18:06
3
$\begingroup$

Proof. Assume $A$ and $(A\lor B)\implies N$ by addition it follows that $A\lor B$ is true and by modus ponens we can reason that $N$ must be true consequently $A\implies N$.

$\blacksquare$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.